Mass [videorecording (DVD)] - Kranz, Fran, 1983-; Birney, Reed, 1954-; Dowd, Ann; Isaacs, Jason, 1963-; Plimpton, Martha, 1970- (Decal, 2022)
Years after an unspeakable tragedy tore their lives apart, two sets of parents agree to talk privately in an attempt to move forward. In Fran Kranz's writing and directing debut, he thoughtfully examines their journey of grief, anger, and acceptance by coming face-to-face with the ones who have been left behind.